2017
DOI: 10.1152/ajpendo.00328.2016
|View full text |Cite
|
Sign up to set email alerts
|

S100B impairs glycolysis via enhanced poly(ADP-ribosyl)ation of glyceraldehyde-3-phosphate dehydrogenase in rodent muscle cells

Abstract: S100 calcium-binding protein B (S100B), a multifunctional macromolecule mainly expressed in nerve tissues and adipocytes, has been suggested to contribute to the pathogenesis of obesity. To clarify the role of S100B in insulin action and glucose metabolism in peripheral tissues, we investigated the effect of S100B on glycolysis in myoblast and myotube cells. Rat myoblast L6 cells were treated with recombinant mouse S100B to examine glucose consumption, lactate production, glycogen accumulation, glycolytic meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Administration of insulin resulted in increased secretion of S100β via PI3K signalling, thus further impairing glucose utilisation. Further in vitro investigations in rat muscle cells by Hosokawa et al (144) in 2017, reported that S100β treatment impaired glycolysis and suppressed glucose utilisation, even in the absence of insulin. This may be a feature of disrupted glycolysis, and impaired brain glucose transport observed in AD brain hypometabolism (145).…”
Section: Role Of S100β In Insulin Resistance?mentioning
confidence: 99%
“…Administration of insulin resulted in increased secretion of S100β via PI3K signalling, thus further impairing glucose utilisation. Further in vitro investigations in rat muscle cells by Hosokawa et al (144) in 2017, reported that S100β treatment impaired glycolysis and suppressed glucose utilisation, even in the absence of insulin. This may be a feature of disrupted glycolysis, and impaired brain glucose transport observed in AD brain hypometabolism (145).…”
Section: Role Of S100β In Insulin Resistance?mentioning
confidence: 99%
“…88,89 In the infarcted heart, S100B, released by surviving cardiomyocytes, might cause cardiomyocyte apoptosis 103 and might promote vascular endothelial growth factor (VEGF) secretion and VEGF-dependent myofibroblast proliferation potentially contributing to scar formation. 116 Notably, muscles of S100B KO mice show reduced levels of poly(ADP-ribosyl)ated GAPDH, 118 but there is no information about the consequences of S100B deletion on muscular performance in terms of muscle strength and resistance to intense physical activity and/or of metabolic rearrangements. 22 Notably, elevated levels of S100B are detected in human serum following intense physical exercise (e.g.…”
Section: Deranged Satellite Cell Propertiesmentioning
confidence: 99%
“…marathon, swimming races, and soccer games). 118 Also, down-regulation of S100B in myoblasts during the first few hours of culture in differentiation medium is permissive for differentiation as persistence of relatively high S100B levels results in the inhibition of myogenic differentiation. [106][107][108] Extracellular effects of S100B are largely brought about by its interaction with RAGE (receptor for advanced glycation end products, encoded by AGER/ Ager) 109,110 ; however, at least in the case of muscle injury, S100B can activate either RAGE or the basic fibroblast growth factor (bFGF)/FGF receptor 1 (FGFR1) complex depending on its own local concentration, myoblast density, and bFGF availability.…”
Section: Deranged Satellite Cell Propertiesmentioning
confidence: 99%
See 2 more Smart Citations